Decontamination Of Endospores By Plasma Sources On Dried Surfaces: A Review Of Key Parameters And Inactivation Results - Salmon, A; Stancu, G. D; Laux, C. O (Frontiers in Physics, 2021)
The efficiency of plasmas sources for the decontamination of heat-sensitive devices has been proven for more than 20 years, but commercial plasma-based sterilizers still have a narrow range of applications. This can be partially explained by difficulties to determine reliable bio-indicators and standardized microbiological test procedures required by industrial uses. In this paper, we examine the influence of environmental factors on the inactivation rate of microorganisms deposited on surfaces and treated by plasma sources. In addition, we present a literature review showing that several in-discharge and afterglow plasma sterilizers offer shorter treatment times than conventional low-temperature sterilizers to reduce the concentration of endospores on contaminated surfaces by 6-log. Finally we make a few recommendations for future plasma decontamination standards.